Kaji Eksperimental Torsi Statik Dan Torsi Dinamik Turbin Hidrokinetik Savonius Type Bach Tiga Sudu - Burhan hafid; Iwan Kurniawan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The potential of hydropower energy in Indonesia is very large, the country of Indonesia has small rivers that continous to flow in the irrigation canal. Hydrokinetic energy can be used in savonius turbines, with the density of water greater than the density of air, the Savonius hydrokinetic turbine can extract sufficient kinetic energy even at low water flow rates.The purpose of this study was to determine the static torque and dynamic torque produced from savonius turbine type of bach three- blades.The hydrokinetic turbines studied were savonius turbine type of bach three- blades with aspect ratio of 1.1, overlap ratio 0.2, rotor height (H) 0.3m, rotor diameter (D) 0.33m, turbine diameter (d) 0, 3m, and with variations in the velocity of water flow (V) 0.3 m / s and 0.65 m / s the test is carried out in a water tunnel. Both of these torsions are obtained in stationary conditions (static torque) for the azimuth each angle and moving conditions (dynamic torque) of no load and until it stops rotating. By utilizing the braking force on pulley with variations in loading. Based on the data obtained, the results of savonius turbine type of bach three- blades. research result in dynamic torque of 0.456 Nm and 0.816 Nm, for the average static torque produced is 0.427 Nm and 0.788 Nm at each azimuth angle.Keywords : Savonius Turbine, Static Torque, Dynamic Torque